Global adaptive linear control of the permanent‐magnet synchronous motor. (22nd July 2013) - Loria, Antonio; Espinosa‐Pérez, Gerardo; Avila‐Becerril, Sofía
SUMMARY We contribute with a linear time‐varying controller for the permanent magnet synchronous motor. We solve the open problem of speed‐tracking control by measuring only stator currents and the rotor angular positions, under parametric uncertainty. Integral action is used to compensate for the effects of the unknown load‐torque, and adaptation is employed to estimate the unknown parameters. In the case that parameters are known (except for the load), we show that the origin of the closed‐loop system is uniformly globally exponentially stable. For the case of unknown parameters, we prove uniform global asymptotic stability; hence, we establish parametric convergence. In contrast to other adaptive control schemes for electrical machines, we use a reduced‐order adaptive controller. Indeed, adaptation is used only for the electrical dynamics equations. Moreover, not surprisingly, the closed‐loop system has a structure well‐studied in adaptive‐control literature. Performance is illustrated in a numerical setting. Copyright © 2013 John Wiley & Sons, Ltd.